Ответ:
Пошаговое объяснение:
(2÷3 1/5 +(3 1/4 ÷13) ÷2/3 +(2 5/18 -17/36)·18/65)·1/3=1/2=0,5
1) 2÷3 1/5=2·5/16=5/8
2) 3 1/4 ÷13=13/4 ·1/13=1/4
3) 1/4 ÷2/3=1/4 ·3/2=3/8
4) 5/8 +3/8=8/8=1
5)2 5/18 -17/36=2 10/36 -17/36=82/36 -17/36=65/36
6) 65/36 ·18/65=1/2
7) 1 +1/2=2/2 +1/2=3/2
8) 3/2 ·1/3=1/2=0,5
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
(2÷3 1/5 +(3 1/4 ÷13) ÷2/3 +(2 5/18 -17/36)·18/65)·1/3=1/2=0,5
1) 2÷3 1/5=2·5/16=5/8
2) 3 1/4 ÷13=13/4 ·1/13=1/4
3) 1/4 ÷2/3=1/4 ·3/2=3/8
4) 5/8 +3/8=8/8=1
5)2 5/18 -17/36=2 10/36 -17/36=82/36 -17/36=65/36
6) 65/36 ·18/65=1/2
7) 1 +1/2=2/2 +1/2=3/2
8) 3/2 ·1/3=1/2=0,5